Children’s Dental Caries Prevention Program: Do Parents Willing to Pay? - Saptutyningsih, Endah; Jati, Hafsah Fajar (Jurnal Ekonomi & Studi Pembangunan, 2022)
This study aims to determine parents’ willingness to pay (WTP) for their children’s dental caries prevention program at elementary school using a direct survey—the Contingent Valuation Method. This study collected data from 264 parents of students aged 6-12 years old (the 1st to the 6th grade). Children at this age are at risk of dental caries because they consume more sweets, chocolate, and other sugary products. The survey results showed that the average WTP value for caries prevention was IDR 103,371. Income, education, and self-perceived needs for treatments were variables that positively and significantly affected WTP. Other variables such as parents’ age and frequency of visiting a dental healthcare facility were insignificant. Oral and dental health treatments can impact not only health during childhood but also in adulthood. The findings can inform health departments in improving dental health services. Research on preventing oral and dental diseases, especially caries, is still limited in Indonesia. Most studies involve adult respondents, whereas this study involves primary school students.